Meningkatkan Hasil Belajar Pendidikan Agama Katolik Melalui Model Pembelajaran Berbasis Masalah - Riah Ukur Damanik (JURNAL GLOBAL EDUKASI, 2021)
Abstract: This research was conducted at SDN 060932 Medan Amplas. The subjects of this study were students in grade 3 SDN 060932 Medan Amplas in the Catholic Religious Education lesson, totaling 28 people, consisting of 13 male students and 15 female students. was given action that the class average score was 69.07 and the percentage of classical completeness was only 25%, In the first cycle action by applying the demonstration method, the class average score was 76.39, the classical completeness percentage was 50% and the student activity observation value showed There was an increase from the initial test in terms of class average and learning completeness, in the second cycle action by applying the PBM model, the class average value increased until it reached 83.39 and the student's observation value increased to reach 85%, With the application of the PBM model can improve student learning outcomes on the Sacrament of Penance material in grade 3 SDN 060932 Medan Amplas academic year 2020/2021. Keywords: based on problems; eucharist; repentance; sacrament of baptism  Abstrak: Penelitian ini dilaksanakan di SDN 060932 Medan Amplas. Subjek penelitian ini adalah siswa kelas 3 SDN 060932 Medan Amplas pada pelajaran Pendidikan Agama Katolik yang berjumlah 28 orang, yang terdiri dari13 orang siswa  laki-laki dan 15 orang siswa perempuan.Berdasarkan dari pembahasan hasil penelitian maka dapat ditarik beberapa simpulan yaitu Pada tes awal sebelum diberikan tindakan bahwa nilai rata-rata kelas 69,07 dan jumlah persentase ketuntasan klasikal hanya 25%, Pada tindakan siklus I dengan penerapan metode demonsrasi diperoleh nilai rata-rata kelas 76,39  persentase ketuntasan klasikal 50% dan nilai observasi aktivitas siswa hal ini menunjukkan adanya peningkatan dari tes awal dari segi rata-rata kelas maupun ketuntasan belajar, Pada tindakan siklus II denagan penerapan model PBM diperoleh nilai rata-rata kelas semakin meningkat hingga mencapai 83,39 dan nilai observasi siswa meningkat sehingga mencapai 85%, Dengan penerapan model PBM dapat meningkatkan hasil belajar siswa pada materi Sakramen Tobat di kelas 3 SDN 060932 Medan Amplas Tahun Pelajaran 2020/2021. Kata Kunci: berbasis masalah; ekaristi; sakramen baptis; tobat